2005
DOI: 10.1016/j.nuclphysa.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical generation of hyperon resonances

Abstract: In this talk we report on how, using a chiral unitary approach for the meson-baryon interactions, two octets of J π = 1/2 − baryon states and a singlet are generated dynamically, resulting in the case of strangeness S = −1 in two poles of the scattering matrix close to the nominal Λ(1405) resonance. We suggest experiments which could show evidence for the existence of these states.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…[21], in which the couplings of the Λ(1670) to the meson-baryon state have already been determined (see table 1 of Ref. [42] for values of the couplings in isospin basis). Thus, because the photon couplings to the mesons and baryons are given by the chiral Lagrangian, there are no free parameters and the helicity amplitudes of the Λ(1670) are pure predictions.…”
Section: Introductionmentioning
confidence: 99%
“…[21], in which the couplings of the Λ(1670) to the meson-baryon state have already been determined (see table 1 of Ref. [42] for values of the couplings in isospin basis). Thus, because the photon couplings to the mesons and baryons are given by the chiral Lagrangian, there are no free parameters and the helicity amplitudes of the Λ(1670) are pure predictions.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of other conjectures regarding the structure of the Λ(1405). It has been suggested that it could be a dynamically generated molecular state ofKN and Σπ [18,[25][26][27][28], or a multi-quark state [29]. Recently, Roca and Oset [30] explained it as a molecular state ofKN .…”
Section: B Comparison With Hqetmentioning
confidence: 99%